The Philosophical Meaning of Pandawa Lima in Wayang (An Analytical Study of Javanese and Islamic Culture) - Ngatmin Abbas; Mukhlis Fathurrohman (Cyber Media Indonesia, 2025)
The Pandawa Lima, as an integral part of Javanese wayang (shadow puppetry), has undergone significant acculturation with the advent of Islamic influence in Java. This phenomenon reflects complex cultural dynamics worthy of deeper study. This research aims to analyze the philosophical meaning of the Pandawa Lima in the context of Javanese-Islamic cultural acculturation and examine its relevance in contemporary society. This study employs a qualitative approach with cultural hermeneutics analysis, supported by John W. Berry's acculturation theory, Clifford Geertz's hermeneutics, Yuri Lotman's cultural semiotics, and Homi Bhabha's concept of hybridity. The analysis shows that the Pandawa Lima serves as a dynamic sign system in Javanese-Islamic culture, creating a unique third space where Javanese and Islamic values are harmoniously integrated. The Pandawa Lima characters represent a synthesis of values relevant to contemporary issues such as ethical leadership, conflict resolution, and social harmony. This acculturation process also offers a model for broader intercultural dialogue, demonstrating how different traditions can synergize without losing their essence.